Smart cleaning servive / Nur Afisha Yusuf ...[et. al] - Yusuf, Nur Afisha; Liakbar, Siti Mas Dewi; Ahmad Zaki, Nadhrah; Awang Jos, Dayang Patinas; Siri, Hazura (2006)
Smart Cleaning Service is a service based company where it provides cleaning services to organization premises. In recent years, more and more organization is depending on other company to keep their premises clean. On the other hand, with the increasing of new establish company, it creates more opportunity for cleaning service company to enter the market. Cleanliness in organization is vital as it affect the workers productivity. When the environment is clean the workers are more likely to do their task (known as job satisfaction). The positive relationship between cleanliness and workers productivity, will lead to increase in productivity. Smart Cleaning Service is committed to supplying the business community with consistent quality maintenance services at below market prices. Unequaled in service, response time and value, our mission is to provide you with the cleaning services that you need to protect and maintain your property. We are in the cleaning business of making your business look good and clean.